(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This study concerns the analysis of consumer Fundamental Rights and its applications. During the search there was the origin of the legal consumer protection in the Brazilian legislation, the constitutional grant and the consequent expansion of legal support. Having been used hermeneutic methodology. Arises, therefore, the question, would consumer Fundamental Rights only contained in the Consumer Protection Code and also in the Constitution? And yet, if it were repealed Consumer Protection Code all Fundamental Rights Consumer would be backed by the Federal Constitution? Key-words: Fundamental rights; consumer; Federal Constitution Consumer Protection Code; protection; legislation; Supreme Court.